Synthesis of carbon nanotubes using natural carbon precursor: Castor oil - Raziah A.Z.; Junizah A.R.; Saifuddin N. (2023)
Castor oil has long been an article of commerce due to its versatility as it is widely used as a starting material for many industrial chemical products because of its unique structure. In this study, carbon nanotubes has been synthesized by thermal decomposition of castor oil in nitrogen atmosphere at 300-400C using custom-made microwave processing unit. The precursor material was catalyzed by iron clusters originating from the addition of ferrocene. The morphology and characterization of the CNTs were studied and discussed by transmission electron microscopy (TEM). 2012 American Institute of Physics.